Factores psicosociales del entorno familiar y su incidencia en el proceso de enseñanza – aprendizaje, de los estudiantes - Muñoz Castillo, Mercy Raquel (2019)
This work consists in identifying the psychosocial factors of the family environment that affect the teaching-learning process of the students. Among the psychosocial factors of the family environment that can be identified are: demotivation, indifference of students, bullying, disinterest of parents, low economic resources, these elements have been detected through the techniques used in the development of the study in this case, such as observation and interview aimed at parents and students. The academic performance of children has a lot to do with the family environment in which they operate, this is that if the environment is pleasant, children feel motivated to exercise their right to education. Otherwise, they do so by obligation what is reflected in their behavior, often inappropriate, which is especially characterized in altering the healthy coexistence and is also reflected in the demotivation by their studies which they trigger with the obtaining of little knowledge and therefore Their qualifications are considered low that many do not reach the required learning and others are close to achieving them